Wage Calculation Scheme for Contract Workers at PT Bersama Sejahtera Sakti Minamas Plantation in Pantai Timur Estate, Kotabaru - Azhar, Noviridhany Maulana; Lidiana, Lidiana; Jamaluddin, Jamaluddin; Witriana, Laili; Asma, Wiszda (Eastasouth Institute, 2025)
The research outlined in this Final Task aims to find out how the Calculation of Wages of Wholesale Workers at PT. Bersama Sejahtera Sakti Minamas Plantation in pantai Timur Estate Kotabaru. the results showed that the calculation of wages for wholesale workers / Wholesale Daily Labor (BHB) who work as brondol citations using two ways, namely, using units of weight (kilograms) for group A and calculated based on the unit of number of sacks for group B. Generally, the payment of wages of brondolan workers in oil palm plantations is known as a wholesale system that uses piecework method and given in cash. Researchers found that this wholesale worker is one form of corporate CSR program as well as the late payment of workers' wages due to the difficulty of access to distribution of brondolan due to the influence of weather and road conditions. After conducting analysis and discussion of the problem the author came to the conclusion that the calculation of wages of wholesale workers at PT. BSS Minamas Plantation went quite well according to the agreement at the beginning of work but wage payments sometimes experience delays and there are differences in the results of the two calculations used so that improvements are needed.